Electrochemiluminescence sensor for dopamine with a dual molecular recognition strategy based on graphite-like carbon nitride nanosheets/3, 4, 9, 10-perylenetetracarboxylic acid hybrids1. Issue 53 (11th June 2015) - Fu, Xiaomin; Feng, Jiahui; Tan, Xingrong; Lu, Qiyi; Yuan, Ruo; Chen, Shihong
<x xml:space="preserve">Abstract</x> Preparation of an ECL sensor and graphite-like carbon nitride nanosheets/3, 4, 9, 10-perylenetetracarboxylic acid hybrids.